2023
DOI: 10.1111/brv.12958
|View full text |Cite
|
Sign up to set email alerts
|

Biotic homogenisation and differentiation as directional change in beta diversity: synthesising driver–response relationships to develop conceptual models across ecosystems

Abstract: Biotic homogenisation is defined as decreasing dissimilarity among ecological assemblages sampled within a given spatial area over time. Biotic differentiation, in turn, is defined as increasing dissimilarity over time. Overall, changes in the spatial dissimilarities among assemblages (termed ‘beta diversity’) is an increasingly recognised feature of broader biodiversity change in the Anthropocene. Empirical evidence of biotic homogenisation and biotic differentiation remains scattered across different ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 659 publications
0
8
0
Order By: Relevance
“…Heterogeneity in range shifts among species has also driven changes in the spatial diversity pattern along the elevation gradient. The reduction in spatial turnover between the low and intermediate sites has caused biotic homogenization at the regional scale (sensu Rolls et al, 2023), as previously observed for other montane organisms (e.g., Ploquin et al, 2013;Savage & Vellend, 2015). Similar patterns have emerged across studies of different global change effects on insect communities, thus pointing to a worrying loss of beta diversity in this taxonomic group (Gossner et al, 2023).…”
mentioning
confidence: 59%
“…Heterogeneity in range shifts among species has also driven changes in the spatial diversity pattern along the elevation gradient. The reduction in spatial turnover between the low and intermediate sites has caused biotic homogenization at the regional scale (sensu Rolls et al, 2023), as previously observed for other montane organisms (e.g., Ploquin et al, 2013;Savage & Vellend, 2015). Similar patterns have emerged across studies of different global change effects on insect communities, thus pointing to a worrying loss of beta diversity in this taxonomic group (Gossner et al, 2023).…”
mentioning
confidence: 59%
“…These findings did not support the third hypothesis and were inconsistent with a recent study conducted in the same region, which indicated that nutrient enrichment led to taxonomic and functional homogenization of macroinvertebrate assemblages in most eutrophic lakes . Although eutrophication increases the importance of environmental filtering and decreases the effects of random processes in structuring biotic communities, the increase (differentiation) or decrease (homogenization) in compositional dissimilarity depends on complex mechanisms (Rolls et al, 2023), including initial ecological conditions, the magnitude and uniformity of disturbances and the sensitivity or tolerance of individual taxa (Chalcraft et al, 2008;Gutiérrez-Cánovas et al, 2013;Hawkins et al, 2015). In our study, despite the higher levels of nutrient concentrations, the algal-dominated (i.e., most eutrophic) lakes showed broader ranges of eutrophication-related water quality (i.e., transparency, TN, TP and Chl a and COD Mn ) than the macrophyte-dominated (or least eutrophic) lakes (Table S6)…”
Section: Discussionmentioning
confidence: 99%
“…G. Hu et al, 2021;Soliveres et al, 2016). It would hamper our mechanistic understanding of processes underlying the observed patterns of spatial variation in soil communities and functions along the gradient of climatic transects (A. S. Mori, Isbell, & Seidl, 2018;Rolls et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the majority of biodiversity-ecosystem function relationship (BEF) studies were emerging from the perspective of single α -diversity and its linkage with local functional levels (Manuel Delgado-Baquerizo et al, 2016; W. G. Hu et al, 2021; Soliveres et al, 2016). It would hamper our mechanistic understanding of processes underlying the observed patterns of spatial variation in soil communities and functions along the gradient of climatic transects (A. S. Mori, Isbell, & Seidl, 2018; Rolls et al, 2023).…”
Section: Introductionmentioning
confidence: 99%